Significance of Triple Detection of p16/ki-67 Dual-Staining, Liquid-Based Cytology and HR HPV Testing in Screening of Cervical Cancer: A Retrospective Study - Yu, Li; Chen, Xun; Liu, Xubin; Fei, Lingyan; Ma, Hanyu; Tian, Tian; Wang, Liantang; Chen, Shangwu (Frontiers in Oncology, 2022)
In addition to liquid-based cytology (LBC) and HR HPV testing, p16/ki-67 dual-staining is another method for cervical cancer screening. The combination of any two methods can improve the accuracy of screening, but some cervical lesions are still missed or misdiagnosed. In this retrospective study, the significance of LBC, HR HPV testing and especially p16/ki-67 dual-staining in cervical lesion screening was evaluated with reference to histological diagnosis. At the same time, we tried to explore the value of p16/ki-67 dual-staining combined with LBC and HR HPV testing (triple detection) in improving the diagnostic specificity of CIN2+ and reducing the missed diagnosis of CIN2+ lesions. We found that p16/ki-67 dual-staining was valuable in identifying cervical CIN2+ lesions and reducing the missed diagnosis of CIN2+ in HPV negative patients. More than 96% of CIN2+ patients were positive for two or three tests of triple detection. Whole positive triple detection can effectively predict high grade cervical lesions. In conclusion, the triple detection can distinguish almost all cervical CIN2+ lesions. Our data put forward and highlight the feasibility and significance of triple detection in cervical lesion screening.